EFFECT OF FAT REPLACERS ON THE QUALITY CHARACTERISTICS OF NON-FAT YOGHURT - V. Thushara; K. Radha; C. T. Sathian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Non-fat yoghurt was prepared by using inulin and whey protein concentrate (WPC) as fat replacers at one and two per cent level. The experimental yoghurts were compared with control yoghurt samples prepared from skim milk and whole milk. pH, titratable acidity, fat, total solids, syneresis, water holding capacity (WHC) and protein contents were studied. Enumeration of viable L. delbrueckii ssp. bulgaricus and S. thermophilus was also carried out. During storage, pH of all the yoghurt samples decreased whereas total solids increased. Addition of inulin  and WPC has controlled the development of acidity during storage. Addition of inulin caused increased syneresis whereas WPC decreased the syneresis percentage. Addition of WPC (2%) has significantly increased the protein percentage and improved the WHC. Both inulin and WPC have increased the Lactobacillus as well as Streptococcus thermophilus count. Non-fat yoghurt incorporated with WPC (2%) had obtained maximum sensory scores.